An eco-friendly water-assisted polyol method to enhance the aspect ratio of silver nanowires. Issue 4 (14th January 2019) - Zhao, Wei; Wang, Sha-Sha; Cao, Hong-Tao; Xie, Ling-Hai; Hong, Chao-Shen; Jin, Ling-Zhi; Yu, Meng-Na; Zhang, He; Zhang, Zhi-Yun; Huang, Li-Hua; Huang, Wei
Abstract : Silver nanowires with a high aspect ratio over 1600 were realized through a water-assisted polyol method. Abstract : With water as an eco-friendly heterogeneous nucleation accelerator, silver nanowires (Ag NWs) have been successfully prepared with a high aspect ratio (>1600). The Ag NW-based film exhibits a low sheet resistance of 8.1 Ω sq −1 with a transparency of 81.9% at 550 nm, showing the potential application of electrode materials in polymer solar cells.